2010
DOI: 10.1136/qshc.2009.033563
|View full text |Cite
|
Sign up to set email alerts
|

Understanding non-adherence in chronic heart failure: a mixed-method case study

Abstract: Quantitative data analysis of treatment regimens in patients with CHF is an inaccurate method for measuring guideline adherence. Combining quantitative prescribing data with semistructured interviews shows a 90% match concerning guideline adherence compared to an only 60% match based on quantitative data alone. Thus, neither quality nor economical assessments of the treatment strategy in patients with chronic diseases should be solely based on quantitative analysis. Understanding non-adherence is crucial for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Most recently, Hirt et al and Oertle et al included a qualitative aspect in their GAI studies and showed that GAI is significantly higher when quantitative as well as qualitative patient data are considered. This supports previous data showing that patient and prescriber factors may be important barriers to guideline adherence .…”
Section: Discussionsupporting
confidence: 89%
“…Most recently, Hirt et al and Oertle et al included a qualitative aspect in their GAI studies and showed that GAI is significantly higher when quantitative as well as qualitative patient data are considered. This supports previous data showing that patient and prescriber factors may be important barriers to guideline adherence .…”
Section: Discussionsupporting
confidence: 89%
“…Patients who present for surgery with significant depressive symptoms and lack of motivation may benefit from established and highly effective methods to improve motivation for following preoperative instructions, rather than efforts to simply make these instructions easier to understand. Similar suggestions have emerged from a recent qualitative study that looked at perspectives on non-adherence between heart failure patients and their treating physicians in which patients perceived themselves as “understanding what to do but needing help with how to carry out [instructions]” whereas doctors perceived patients as “not understanding… and therefore needing more repetition of knowledge-based instructions.” 61 The present study offers some support to the generalizability of such findings to the preoperative physician-patient encounter.…”
Section: Discussionsupporting
confidence: 69%
“…12 Prevalent themes in a mixed-methods study aimed at understanding nonadherence in HF included clinical constraints related to low blood pressure or heart rate and renal dysfunction; uncertainty about treatments and symptom improvement; omissions and errors with drugs and drug dosing; patient factors related to comorbidities, polypharmacy, and adherence when multiple changes (increase and decrease) in drug doses were made by 386 Circ Heart Fail March 2015 healthcare providers; and lack of collaboration from inpatient to outpatient care, especially related to medications. 13 Similar themes related to physical, psychological, economic, social, and behavioral (self-care) quality of life (QoL) were brought forward when patients with symptomatic HF were interviewed to understand perceived QoL.…”
Section: Patient Characteristics and Unmet Needsmentioning
confidence: 99%